# Solve for y 8y+4(5+y)=3(y-2(10y)) 8y+4(5+y)=3(y-2(10y))
Simplify 8y+4(5+y).
Simplify each term.
Apply the distributive property.
8y+4⋅5+4y=3(y-2(10y))
Multiply 4 by 5.
8y+20+4y=3(y-2(10y))
8y+20+4y=3(y-2(10y))
Add 8y and 4y.
12y+20=3(y-2(10y))
12y+20=3(y-2(10y))
Simplify 3(y-2(10y)).
Multiply 10 by -2.
12y+20=3(y-20y)
Subtract 20y from y.
12y+20=3(-19y)
Multiply -19 by 3.
12y+20=-57y
12y+20=-57y
Move all terms containing y to the left side of the equation.
Add 57y to both sides of the equation.
12y+20+57y=0
Add 12y and 57y.
69y+20=0
69y+20=0
Subtract 20 from both sides of the equation.
69y=-20
Divide each term by 69 and simplify.
Divide each term in 69y=-20 by 69.
69y69=-2069
Cancel the common factor of 69.
Cancel the common factor.
69y69=-2069
Divide y by 1.
y=-2069
y=-2069
Move the negative in front of the fraction.
y=-2069
y=-2069
The result can be shown in multiple forms.
Exact Form:
y=-2069
Decimal Form:
y=-0.28985507…
Solve for y 8y+4(5+y)=3(y-2(10y))

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top